Analisis Brand Image Dan Brand Equity Terhadap Loyalitas Konsumen Smartphone Samsung (Studi Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Guritno, Adi Kuncoro Suryo, Dr. Rini Kuswati, S.E., M.Si (2016)
This research was conducted at Economics and Business Faculty University Muhammadiyah Surakarta which aims to analyze Brand Image on costomer loyalty smartphone Samsung, analyzing Brand Equity on costomer loyalty smartphone Samsung, analyzing Brand Image and Brand Equity on costomer loyalty smartphone Samsung. This study uses the survey design, the research took a sample from a population by using a questionnaire. The sample used were 100 college student at Economics and Business Faculty University uhammadiyah Surakarta. Methods of data collection in this study using a qushionnaire. The analytical tool used in this research is to test the instrument, the classical assumption test, data analysis (multiplt linear regression analysis, t-test, f and coefficient of determindtion (R2)) The results of data analysis can be obtained there are significant Brand Image positive and significant on ostomer loyalty smartphone Samsung on college student at Economics and Business Faculty University Muhammadiyah Surakarta, there are significant Brand Equity positive and significant on costomer loyalty smartphone Samsung on college student at Economics and Business Faculty University Muhammadiyah Surakarta, and there are Brand Image and Brand Equity simultaneously on costomer loyalty.